2021
DOI: 10.1136/bmjopen-2021-050109
|View full text |Cite
|
Sign up to set email alerts
|

What can be learnt from a qualitative evaluation of implementing a rapid sexual health testing, diagnosis and treatment service?

Abstract: ObjectivesTo investigate experiences of implementing a new rapid sexual health testing, diagnosis and treatment service.DesignA theory-based qualitative evaluation with a focused ethnographic approach using non-participant observations and interviews with patient and clinic staff. Normalisation process theory was used to structure interview questions and thematic analysis.SettingA sexual health centre in Bristol, UK.Participants26 patients and 21 staff involved in the rapid sexually transmitted infection (STI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…These improvements, while maintaining activity at a lower overall cost, suggests that the introduction of clinic-based rapid testing had the intended impact, and this is in line with previous NPT modelling studies [10,11]. The qualitative evaluation of this rapid STI service also reported that patients valued faster results and avoiding unnecessary treatment, and that the better targeting of infection-specific treatment improved antimicrobial stewardship [29].…”
Section: Implications and Conclusionsupporting
confidence: 73%
See 4 more Smart Citations
“…These improvements, while maintaining activity at a lower overall cost, suggests that the introduction of clinic-based rapid testing had the intended impact, and this is in line with previous NPT modelling studies [10,11]. The qualitative evaluation of this rapid STI service also reported that patients valued faster results and avoiding unnecessary treatment, and that the better targeting of infection-specific treatment improved antimicrobial stewardship [29].…”
Section: Implications and Conclusionsupporting
confidence: 73%
“…In light of the target trial framework for natural experiments[30], our study was limited by being non-randomised, having only one control site, relying on the construction of certain outcomes from multiple variables, and the impact of the Covid-19 pandemic on the follow up period for females. The unit costs were based on data provided by Unity SHS and estimates from literature, and commissioners will need to assess their applicability to their locality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations